Film and method for producing the same

By adding 20% ​​or more aromatic-aliphatic copolyester to the biodegradable plastic film and adjusting the heterogeneity parameters on the film surface, the problem that existing films are difficult to achieve easy tear and strength at the same time is solved, and the effect of easy-to-open packaging materials is achieved.

JP2025060486APending Publication Date: 2025-04-10MITSUBISHI CHEM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024169179
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-27
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

When used as packaging materials, it is difficult to achieve the strength required for easy tear and packaging in one direction at the same time.

Method used

The linear tearing performance of the film is improved by including 20% ​​or more aromatic-aliphatic copolyester in the plastic film and by measuring polarized Raman spectra, the heterogeneity parameters on the film surface are adjusted to achieve a specific ratio.

Benefits of technology

It realizes the tearability and strength of the biodegradable film in the packaging material, and meets the needs of easy-to-open packaging material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060486000001
    Figure 2025060486000001
Patent Text Reader

Abstract

To provide a film which achieves both easy tearing property in one direction and strength required as a packaging material, and a method for producing the same.SOLUTION: A stretched film is composed of a resin composition containing aliphatic-aromatic polyester, and contains 20 mass% or more of the aliphatic-aromatic polyester, wherein the aliphatic-aromatic polyester includes a structural unit derived from a terephthalic acid, out of anisotropic parameters AP determined by measuring polarization Raman spectrum of the surface of the film, a ratio APmax / APorg represented by APmax and APorg measured by the following evaluation method is 1.25 or more. (Measurement method) When peak areas corresponding to stretching vibration of a benzene ring and a methylene group derived from a terephthalic acid unit are represented by I1612 and I2850, anisotropic parameters measured in a direction at which a ratio represented by I1612 / I2850 becomes maximum and a direction perpendicular to the direction out of directions at arbitrary angles are represented by APmax and APorg.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film and a method for producing the same. [Background technology]

[0002] Plastic films are widely used as packaging materials. Currently, efforts are being made to recycle plastic packaging materials, but each household must separate the materials and, in some cases, wash the contents, which is time-consuming and hinders the effective use of resources. In addition, if plastic is released into the environment, it will remain for a long time, which is also a problem from the perspective of environmental protection. As a solution to these problems, the use of biodegradable plastics is being promoted. Biodegradable packaging materials can be composted by being thrown into a composting facility together with food waste without the need for separation or washing. In addition, even if they do leak into the environment, the period they remain can be shortened. Furthermore, biodegradable resins derived from biomass are also beneficial from the perspective of reducing carbon dioxide emissions.

[0003] In order to use biodegradable plastic films as packaging materials, various properties such as formability and impact resistance are required. Aliphatic-aromatic polyesters such as polybutylene adipate terephthalate (PBAT) are known to have all of these properties. Furthermore, in the case of packaging materials used at home, it would be more useful if they could not only protect the contents but also be easily torn in a straight line by hand. Patent Document 1 discloses that a biodegradable protective film is provided that is easy to tear and peel in the TD direction by mixing aliphatic polyester resin and / or aromatic polyester resin, inorganic filler, and lubricant in a specific ratio and then inflation molding the mixture at a specific blow ratio. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2007-002011 Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, in order to be more useful as a packaging film, it is required that the film has both appropriate tearability and strength. The protective film described in Patent Document 1 has the required strength, peelability, and ease of tearing in the TD direction, but as an easy-open packaging material, it is insufficient in terms of ease of tearing linearly in one direction.

[0006] In view of the above problems, the present invention has an object to provide a film that is easy to tear in one direction while also having the strength required for a packaging material, and a method for producing the same. [Means for solving the problem]

[0007] As a result of investigations into the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by containing a specific amount or more of an aliphatic-aromatic polyester containing a structural unit derived from terephthalic acid, and by setting the ratio of the anisotropy parameter AP in a specific direction to the anisotropy parameter AP in a direction perpendicular thereto within a specific range, among the anisotropy parameters AP determined by measuring the polarized Raman spectrum of the film surface, and thus completed the present invention.

[0008] That is, the gist of the present invention resides in the following items. [1] A film made of a resin composition containing an aliphatic-aromatic polyester, Contains 20% by mass or more of an aliphatic-aromatic polyester, the aliphatic-aromatic polyester comprises constitutional units derived from terephthalic acid, Among the anisotropy parameters AP obtained by measuring the polarized Raman spectrum of the film surface, AP measured by the following evaluation method max and APоrg The ratio AP expressed as max / AP оrg is 1.25 or more. (Evaluation method) In a microscopic laser Raman spectrometer, a linearly polarized laser beam with a wavelength of 633 nm, in which a 1 / 2 λ plate is inserted to set the direction of polarization (direction of vibration of the electric field) at an arbitrary angle, is made to enter the film surface perpendicularly, and the spectrum of the generated Raman scattered light is measured. -1 The area of ​​the Raman band with a peak near I 1612 and 2850 cm, which corresponds to the stretching vibration of the methylene group in the polymer chain. -1 The area of ​​the Raman band with a peak near I 2850 In this case, among the directions of the arbitrary angle, I 1612 / I 2850 The anisotropy parameter measured in the direction where the ratio is maximum is AP max and the anisotropy parameter measured in the direction perpendicular to the direction is AP оrg Let us assume that. [2] Measured according to ISO 6383-2, AP max The tear strength in the direction in which the tear was measured divided by the thickness of the film (TR 1 ) is 70N / mm or more, оrg The tear strength in the direction in which the tear was measured divided by the thickness of the film (TR 2 ) is TR 1 The film according to [1], wherein the thickness is 1 / 10 or less of the thickness of the film. [3] The film described in [1] or [2], wherein the resin composition further contains an aliphatic polyester. [4] The film according to [3], wherein the aliphatic polyester is a polyester containing aliphatic diol units and aliphatic dicarboxylic acid units as main constituent units. [5] The film according to [3] or [4], wherein the aliphatic polyester contains, as a constituent unit, one or more aliphatic dicarboxylic acid units selected from the group consisting of succinic acid units, adipic acid units, and sebacic acid units. [6] The film according to any one of [1] to [5], wherein the aliphatic-aromatic polyester contains a structural unit derived from 1,4-butanediol and a structural unit derived from succinic acid. [7] The film according to any one of [1] to [6], wherein the resin composition has a bio-based carbon content of 20% or more as measured in accordance with ISO 16620-2. [8] An easy-open packaging material comprising the film according to any one of [1] to [7]. [9] A method for producing a film according to any one of [1] to [7], The method includes a molding step of extruding the resin composition containing the aliphatic-aromatic polyester through a die lip and performing inflation molding to obtain a film, In the molding step, the gap d (mm) of the die lip, the blow ratio B, and the thickness t (mm) of the molded film satisfy the following formula (1): A method for manufacturing a film. d / (B 2 ×t)≧3 (1) Effect of the Invention

[0009] According to the present invention, it is possible to provide a biodegradable film that is easy to tear in one direction and has the strength required for a packaging material, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The following describes in detail the embodiments of the present invention; however, the present invention is not limited to the following description, and can be modified in any manner without departing from the gist of the present invention. In this specification, when "~" is used to express a numerical value or a physical property value, the values ​​before and after the "~" are included. In addition, in this specification, the expression "A or B" can be read as "at least one selected from the group consisting of A and B." In this specification, "mass %" and "parts by mass" have the same meaning as "weight %" and "parts by weight", respectively. In addition, although a number of embodiments are described in this specification, various conditions in each embodiment may be applied to each other to the extent that they are applicable.

[0011] In this specification, the polyester resin is a polymer having repeating units, and each repeating unit is also called a compound unit corresponding to the compound from which the repeating unit is derived. For example, a repeating unit derived from an aliphatic diol is also called an "aliphatic diol unit," and a repeating unit derived from an aliphatic dicarboxylic acid is also called an "aliphatic dicarboxylic acid unit." In this specification, the term "main structural unit" in a resin generally refers to a structural unit that is contained in the resin at 51% by mass or more, and this proportion is preferably 70% by mass or more, more preferably 80% by mass or more, and may be 100% by mass (no structural units other than the main structural unit are contained). In addition, "resin R contains A units and B units as main structural units" means that the total content of A units and B units in resin R is 51% by mass or more.

[0012] <Film Composition> The film according to one embodiment of the present invention (hereinafter also simply referred to as "film") has A film made of a resin composition containing an aliphatic-aromatic polyester, Contains 20% by mass or more of an aliphatic-aromatic polyester, the aliphatic-aromatic polyester comprises constitutional units derived from terephthalic acid, Among the anisotropy parameters AP obtained by measuring the polarized Raman spectrum of the film surface, AP measured by the following evaluation method max and AP оrg The ratio AP expressed as max / AP оrg is 1.25 or more. (Evaluation method) In a microscopic laser Raman spectrometer, a linearly polarized laser beam with a wavelength of 633 nm, in which a 1 / 2 λ plate is inserted to set the direction of polarization (direction of vibration of the electric field) at an arbitrary angle, is made to enter the film surface perpendicularly, and the spectrum of the generated Raman scattered light is measured. -1 The area of ​​the Raman band with a peak near I 1612 and 2850 cm, which corresponds to the stretching vibration of the methylene group in the polymer chain. -1 The area of ​​the Raman band with a peak near I 2850 In this case, among the directions of the arbitrary angle, I 1612 / I 2850 The anisotropy parameter measured in the direction where the ratio is maximum is AP max and the anisotropy parameter measured in the direction perpendicular to the direction is AP оrg Let us assume that.

[0013] The anisotropy parameter AP is determined by the orientation (arrangement) of the crystals consisting of terephthalic acid units and diol units. max / AP оrg The larger the value of is, the more the crystal orientation of the film is aligned in one direction, and the easier it is to tear the film linearly in one direction. Since film destruction is generally thought to occur from the surface, it is particularly preferable that the anisotropy parameter measured by irradiating the film surface with a laser beam is within the above range.

[0014] AP max / AP оrg is not particularly limited as long as it is 1.25 or more, but from the viewpoint of improving the ease of tearing in one direction, it is preferably 1.30 or more, more preferably 1.35 or more, even more preferably 1.40 or more, and particularly preferably 1.50 or more. The upper limit of this ratio is also preferably 1.30 or more, since the film is excessively weak in one direction and is likely to tear. From the viewpoint of preventing the surface roughness from increasing, the surface roughness is preferably 1.70 or less, more preferably 1.65 or less, further preferably 1.60 or less, and particularly preferably 1.55 or less.

[0015] The shape of the film is not particularly limited and can be appropriately set depending on the application. For example, the shape may be a sheet or a bag.

[0016] The thickness of the film is not particularly limited and can be set appropriately depending on the application; however, from the viewpoint of ensuring sufficient strength and gas barrier properties, it is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, and particularly preferably 25 μm or more; and from the viewpoint of ensuring flexibility and biodegradability, it is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, and particularly preferably 70 μm or less. The size of the film in the planar direction is not particularly limited, and can be appropriately set depending on the application.

[0017] The method of irradiating the linearly polarized laser light is not particularly limited, and a known laser light irradiation device can be used.

[0018] In this specification, a "film made of a resin composition" can be rephrased as a "film composed only of a resin composition", and since a resin composition containing an aliphatic-aromatic polyester and a film are similar subjects, the conditions of the resin composition can be treated as the conditions of the film.

[0019] [Aliphatic-aromatic polyester] The resin composition includes an aliphatic-aromatic polyester. The aliphatic-aromatic polyester resin is a polyester resin including, as main constituent units, a repeating unit derived from an aliphatic diol, a repeating unit derived from an aliphatic dicarboxylic acid, and a repeating unit derived from an aromatic dicarboxylic acid. The aliphatic-aromatic polyester is preferably crystalline. The aliphatic-aromatic polyester may be used alone or in combination of two or more kinds. The structure of the aliphatic-aromatic polyester is as follows: 1 It can be identified by H-NMR, pyrolysis gas chromatography, etc.

[0020] In this specification, the aliphatic diol refers to an aliphatic hydrocarbon group to which two hydroxyl groups are bonded, and may be a derivative of an aliphatic diol. As the aliphatic hydrocarbon group, a straight-chain aliphatic hydrocarbon group is usually used, but it may have a branched structure, a cyclic structure, or a plurality of these structures. Furthermore, the term "aliphatic dicarboxylic acid" refers to an aliphatic hydrocarbon group to which two carboxyl groups are bonded, and is a general term for aliphatic dicarboxylic acids such as aliphatic dicarboxylic acid and aliphatic dicarboxylic acid derivatives such as aliphatic dicarboxylic acid alkyl esters. As the aliphatic hydrocarbon group, a straight-chain aliphatic hydrocarbon group is usually used, but it may have a branched structure, a cyclic structure, or a plurality of these. In addition, the aromatic dicarboxylic acid refers to an aromatic hydrocarbon group to which two carboxyl groups are bonded, and is a general term for aromatic dicarboxylic acids such as aromatic dicarboxylic acid and aromatic dicarboxylic acid derivatives such as aromatic dicarboxylic acid alkyl esters. As the aromatic hydrocarbon group, a phenylene group is usually used, but the aromatic ring may have a substituent, may have multiple substituents, or may have multiple aromatic rings. In the present invention, the aromatic dicarboxylic acid is a broad aromatic dicarboxylic acid including heteroaromatic dicarboxylic acids.

[0021] The aliphatic diol unit, the aliphatic dicarboxylic acid unit, and the aromatic dicarboxylic acid unit may be, for example, an aliphatic diol unit represented by the following formula (1), an aliphatic dicarboxylic acid unit represented by the following formula (2), and an aromatic dicarboxylic acid unit represented by the following formula (3), respectively. -OR 1 -O- ···(1) (In formula (1), R 1represents a divalent aliphatic hydrocarbon group. -OC-R 2 -CO- ···(2) (In formula (2), R 2 represents a divalent aliphatic hydrocarbon group. -OC-R 3 -CO- ···(3) (In formula (3), R 3 represents a divalent aromatic hydrocarbon group.

[0022] The content of the aliphatic-aromatic polyester in the resin composition is not particularly limited as long as it is 20% by mass or more from the viewpoint of providing strength and elongation sufficient for use, but is usually 30% by mass or more, preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, and the upper limit is not particularly limited and may be 100% by mass.

[0023] Each of the structural units contained in the aliphatic-aromatic polyester will be described in detail below.

[0024] (diol unit) The structure of the diol unit contained in the aliphatic-aromatic polyester is not particularly limited as long as it contains at least an aliphatic diol unit, and may contain an aromatic diol. As the diol that gives the diol unit, any diol that is usually used as a raw material for polyesters can be used without any particular limitation. The structure of the diol may be a straight chain structure, a branched chain structure, or a ring structure.

[0025] The total content of diol units in the aliphatic-aromatic polyester is not particularly limited, but from the viewpoint of fluidity and melt tension, it is usually 10 mol% or more, preferably 30 mol% or more, more preferably 40 mol% or more, and even more preferably 45 mol% or more, relative to 100 mol% of all structural units constituting the aliphatic-aromatic polyester, and is usually 60 mol% or less, and preferably 55 mol% or less.

[0026] The number of carbon atoms in the aliphatic diol is not particularly limited, but is usually 2 to 20. From the viewpoints of moldability, mechanical strength, and controlling the content of ester groups within a desired range, the number of carbon atoms is preferably 2 to 12, more preferably 2 to 6, and particularly preferably 2 to 4.

[0027] Examples of the aliphatic diol include alkylene diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and neopentyl glycol; oxyalkylene diols such as diethylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol; and cycloalkylene diols such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol. Among these, from the viewpoint of biodegradability, ethylene glycol, 1,3-propanediol, or 1,4-butanediol is preferred, ethylene glycol or 1,4-butanediol is more preferred, and 1,4-butanediol is particularly preferred from the viewpoint of being easily crystallized and obtaining excellent strength and moldability. These aliphatic diols may or may not be derivatives thereof. The aliphatic diol unit may have a structure in which one kind or two or more kinds are mutually dehydrated and condensed.

[0028] The total content of aliphatic diol units in the aliphatic-aromatic polyester is not particularly limited, but from the viewpoint of fluidity and melt tension, it is usually 10 mol% or more, preferably 30 mol% or more, more preferably 40 mol% or more, and even more preferably 45 mol% or more, relative to 100 mol% of all structural units constituting the aliphatic-aromatic polyester, and is usually 60 mol% or less, and preferably 55 mol% or less.

[0029] The aliphatic-aromatic polyester may contain aromatic diol units. Specific examples of aromatic diols include xylylene glycol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, bis(4-β-hydroxyethoxyphenyl)sulfonic acid, etc. These aromatic diols may or may not be derivatives of these. The aromatic diol unit may have a structure in which one or more kinds of aromatic diol units are dehydrated and condensed with each other, or may have a structure in which the aromatic diol unit is dehydrated and condensed with the above-mentioned aliphatic diol.

[0030] The diol that gives the diol unit may be derived from a compound derived from a fossil fuel or from a compound derived from a plant raw material, but is preferably derived from a compound derived from a plant raw material. For example, ethylene glycol, 1,3-propanediol, 1,4-butanediol, etc., derived from a plant raw material can be used.

[0031] (dicarboxylic acid unit) The structure of the dicarboxylic acid units contained in the aliphatic-aromatic polyester is not particularly limited as long as it contains at least an aliphatic dicarboxylic acid unit and an aromatic dicarboxylic acid unit. As the dicarboxylic acid that gives the dicarboxylic acid unit, any dicarboxylic acid that is usually used as a raw material for polyesters can be used without any particular limitation. The structure of the dicarboxylic acid may be a straight chain structure, a branched chain structure, or a ring structure.

[0032] The total content of dicarboxylic acid units in the aliphatic-aromatic polyester is not particularly limited, but from the viewpoint of flowability and melt tension, it is usually 10 mol% or more, preferably 30 mol% or more, more preferably 40 mol% or more, and even more preferably 45 mol% or more, relative to 100 mol% of all constituent units constituting the aliphatic-aromatic polyester, and is usually 90 mol% or less, preferably 70 mol% or less, more preferably 60 mol% or less, and even more preferably 55 mol% or less.

[0033] The number of carbon atoms in the aliphatic dicarboxylic acid is not particularly limited, but is usually 2 to 36, preferably 3 to 12, more preferably 3 to 10, further preferably 3 to 6, and particularly preferably 4. When the carbon number of the aliphatic dicarboxylic acid is equal to or greater than the lower limit of the above range, good moldability can be obtained, whereas when the carbon number of the aliphatic dicarboxylic acid is equal to or less than the upper limit of the above range, mechanical properties can be further improved.

[0034] Examples of aliphatic dicarboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, succinic anhydride, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, brassylic acid, maleic acid, fumaric acid, and dimer acid. Among these, from the viewpoint of thermal stability and crystallinity, succinic acid, succinic anhydride, adipic acid, and sebacic acid are preferred, and succinic acid and adipic acid are more preferred. Of these, succinic acid is particularly preferred. The aliphatic dicarboxylic acid unit may have a structure in which one kind or two or more kinds are mutually dehydrated and condensed.

[0035] The total content of aliphatic dicarboxylic acid units in the aliphatic-aromatic polyester is not particularly limited, but from the viewpoint of obtaining appropriate flexibility and biodegradability, it is usually 10 mol% or more, preferably 13 mol% or more, more preferably 16 mol% or more, and even more preferably 18 mol% or more, relative to 100 mol% of all structural units constituting the aliphatic-aromatic polyester; and from the viewpoint of obtaining good crystallinity, strength, and moldability, it is usually 40 mol% or less, preferably 37 mol% or less, more preferably 34 mol% or less, and even more preferably 32 mol% or less.

[0036] The number of carbon atoms in the aromatic dicarboxylic acid is not particularly limited, but is usually 6-30, preferably 6-25, more preferably 6-15, and further preferably 6-8. When the carbon number of the aromatic dicarboxylic acid is equal to or greater than the lower limit of the above range, the thermal stability can be improved. When the carbon number of the aromatic dicarboxylic acid is equal to or less than the upper limit of the above range, the moldability can be improved.

[0037] Specific examples of aromatic dicarboxylic acids include terephthalic acid, 2,5-furandicarboxylic acid, phthalic acid, isophthalic acid, dibromoisophthalic acid, sulfoisophthalic acid, 1,4-phenylenedioxydicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-diphenylketonedicarboxylic acid, 4,4'-diphenoxyethanedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, hexahydrophthalic acid, hexahydroisophthalic acid, and hexahydroterephthalic acid. Among these, terephthalic acid, 2,5-furandicarboxylic acid, and isophthalic acid are preferred from the viewpoint of obtaining appropriate flexibility and crystallinity, and terephthalic acid is particularly preferred. These aromatic dicarboxylic acids may be derivatives of these or may not be derivatives. For example, derivatives of the aromatic dicarboxylic acids exemplified above are preferred, and among them, lower alkyl esters having 1 to 4 carbon atoms or less, acid anhydrides, etc. are included. Specific examples of derivatives of aromatic dicarboxylic acid compounds include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the aromatic dicarboxylic acids exemplified above; and cyclic acid anhydrides of the aromatic dicarboxylic acids exemplified above, such as succinic anhydride.

[0038] The dicarboxylic acid that gives the dicarboxylic acid unit may be derived from a compound derived from a fossil fuel or from a compound derived from a plant raw material, but is preferably derived from a compound derived from a plant raw material. For example, succinic acid or sebacic acid derived from a plant raw material can be used.

[0039] The total content of aromatic dicarboxylic acid units in the aliphatic-aromatic polyester is not particularly limited, but from the viewpoint of obtaining good crystallinity, strength, and moldability, it is usually 10 mol% or more, preferably 13 mol% or more, more preferably 16 mol% or more, and even more preferably 18 mol% or more, relative to 100 mol% of all structural units constituting the aliphatic-aromatic polyester; and from the viewpoint of obtaining biodegradability and appropriate flexibility, it is usually 40 mol% or less, preferably 37 mol% or less, more preferably 34 mol% or less, and even more preferably 32 mol% or less.

[0040] The ratio (molar ratio) of the dicarboxylic acid units in the aliphatic-aromatic polyester, that is, the aliphatic dicarboxylic acid units and the aromatic dicarboxylic acid units, is preferably 10:90 to 90:10. It is preferable that the ratio is 30:70 to 70:30, more preferably 40:60 to 60:40, and particularly preferably 45:55 to 55:45. If the ratio of the aliphatic dicarboxylic acid unit is less than the above lower limit and the ratio of the aromatic dicarboxylic acid unit is more than the above upper limit, the biodegradability of the aliphatic-aromatic polyester is impaired and flexibility tends to be insufficient. If the ratio of the aliphatic dicarboxylic acid unit is more than the above upper limit and the ratio of the aromatic dicarboxylic acid unit is less than the above lower limit, heat resistance is reduced and mechanical strength and moldability tend to be insufficient. That is, if the aliphatic-aromatic polyester has the ratio (molar ratio) of the aliphatic dicarboxylic acid unit to the aromatic dicarboxylic acid unit in the above specific ratio, it exhibits particularly excellent properties in terms of biodegradability, heat resistance, flexibility, etc. The molar ratio and the content of the aliphatic oxycarboxylic acid unit are as follows: 1 It can be determined from the integral value obtained by H-NMR measurement.

[0041] It is most preferable that the combination of the aliphatic diol unit and the aromatic dicarboxylic acid unit in the aliphatic-aromatic polyester contains both 1,4-butanediol unit and terephthalic acid unit. The constitutional unit consisting of 1,4-butanediol unit and terephthalic acid unit has a particularly fast crystallization rate, and therefore, by forming crystals quickly during molding, good moldability and mechanical strength can be obtained.

[0042] (Other copolymer components) In producing the aliphatic-aromatic polyester, the components shown below may be copolymerized as constituent components (other copolymerization components) other than the above diol and dicarboxylic acid.

[0043] The aliphatic-aromatic polyester may have a repeating unit (aliphatic oxycarboxylic acid unit) derived from an aliphatic oxycarboxylic acid. Specific examples of the aliphatic oxycarboxylic acid component that gives the aliphatic oxycarboxylic acid unit include, for example, lactic acid, glycolic acid, 2-hydroxy-n-butyric acid, 2-hydroxycaproic acid, 6-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, and the like, or derivatives thereof such as lower alkyl esters or intramolecular esters. When optical isomers exist in these, they may be any of D-form, L-form, or racemic form, and may be in the form of a solid, liquid, or aqueous solution. Among these, lactic acid or glycolic acid or derivatives thereof are particularly preferred. These aliphatic oxycarboxylic acids may be used alone or as a mixture of two or more.

[0044] When the aliphatic-aromatic polyester contains an aliphatic oxycarboxylic acid unit, the content thereof is preferably 10 mol % or less, more preferably 5 mol % or less, even more preferably 2 mol % or less, and most preferably 0 mol % (not contained or below the detection limit), based on 100 mol % of all constituent units constituting the polyester resin (A), from the viewpoint of moldability.

[0045] In addition, from the viewpoint of film formability, it is preferable that the aliphatic-aromatic polyester has an increased melt viscosity by copolymerizing a trifunctional or higher aliphatic polyhydric alcohol, a trifunctional or higher aliphatic polycarboxylic acid or its acid anhydride, or a trifunctional or higher aliphatic polyoxycarboxylic acid component.

[0046] Specific examples of trifunctional aliphatic polyhydric alcohols include trimethylolpropane and glycerin, and specific examples of tetrafunctional aliphatic polyhydric alcohols include pentaerythritol. These may be used alone or in combination of two or more. Among these, trimethylolpropane and glycerin are preferred, and trimethylolpropane is more preferred.

[0047] Specific examples of trifunctional aliphatic polycarboxylic acids or their acid anhydrides include propane tricarboxylic acid, Specific examples of tetrafunctional polyvalent carboxylic acids or their anhydrides include cyclopentanetetracarboxylic acid or its anhydride, etc. These may be used alone or in combination of two or more.

[0048] In addition, trifunctional aliphatic oxycarboxylic acids are divided into (i) a type having two carboxyl groups and one hydroxyl group in the same molecule, and (ii) a type having one carboxyl group and two hydroxyl groups. Either type can be used, but from the viewpoint of moldability, mechanical strength, and appearance of molded products, (i) a type having two carboxyl groups and one hydroxyl group in the same molecule, such as malic acid, is preferred, and more specifically, malic acid is preferably used. In addition, tetrafunctional aliphatic oxycarboxylic acid components are divided into (i) a type having three carboxyl groups and one hydroxyl group in the same molecule, (ii) a type having two carboxyl groups and two hydroxyl groups in the same molecule, and (iii) a type having three hydroxyl groups and one carboxyl group in the same molecule. Either type can be used, but those having multiple carboxyl groups are preferred, and more specifically, citric acid, tartaric acid, etc. can be mentioned. These can be used alone or in a mixture of two or more types.

[0049] The aliphatic-aromatic polyester may contain each of the above-mentioned structural units, and specific examples thereof include polybutylene succinate terephthalate (PBST), polybutylene adipate terephthalate (PBAT), polyethylene succinate terephthalate (PEST), polybutylene sebacate terephthalate (PBSeT), etc. Among these, from the viewpoint of obtaining a resin composition excellent in moldability and mechanical strength, polybutylene succinate terephthalate or polybutylene adipate terephthalate is preferred, and polybutylene succinate terephthalate consisting of units of 1,4-butanediol, succinic acid, and terephthalic acid is particularly preferred.

[0050] [Characteristics of aliphatic-aromatic polyesters] (Bio-based carbon content) The bio-based carbon content of the aliphatic-aromatic polyester measured by ISO 16620-2 is not particularly limited, but from the viewpoint of suppressing carbon dioxide emissions, it is preferably 20% or more, more preferably 35% or more, and even more preferably 50% or more. The upper limit does not need to be set, and may be 100%, 80% or less, 70% or less, or 60% or less. By increasing the bio-based carbon content, it is possible to suppress the consumption of fossil fuels and reduce the amount of carbon dioxide emissions, which is beneficial from the viewpoint of protecting the global environment. In addition, in the composition according to this embodiment, it is preferable that the above-mentioned range of the bio-based carbon content is satisfied by the entire components contained in the composition. The bio-based carbon content can be controlled by adjusting the ratio of monomer units produced from plant-derived raw materials to the total structural units constituting one or more polyesters. The bio-based carbon content may be satisfied by one polyester contained in the composition, or may be satisfied by the entire one or more polyesters, and is preferably satisfied by at least one polyester. The bio-based carbon content above is calculated based on the carbon-14( 14 C) from the bio-based carbon content and polymerization ratio of each of the raw materials, the aliphatic diol component, the aliphatic dicarboxylic acid component, and the aromatic dicarboxylic acid component. In this specification, the term "biodegradable resin (polyester)" does not necessarily mean that the entirety of one type of resin (polyester) is biodegradable, but rather that only a portion of the one type of resin (polyester) is biodegradable, and it is preferable that the resin satisfy the above-mentioned range of biodegradability, for example.

[0051] (molecular weight) The molecular weight of the aliphatic-aromatic polyester is not particularly limited, but can be measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the aliphatic-aromatic polyester, using monodisperse polystyrene as the standard substance, is usually 10,000 or more and 1,000,000 or less. However, because this is advantageous in terms of moldability and mechanical strength, it is preferably 20,000 or more and 500,000 or less, more preferably 50,000 or more and 400,000 or less, and even more preferably 100,000 or more and 300,000 or less.

[0052] (Melt Flow Rate) The melt flow rate (MFR) of the aliphatic-aromatic polyester is not particularly limited, but is a value measured at 190 ° C. and a load of 2.16 kg based on JIS K7210 (2014), and is usually 0.1 g / 10 minutes or more and 100 g / 10 minutes or less, but from the viewpoint of moldability and mechanical strength, it is preferably 40 g / 10 minutes or less, more preferably 20 g / 10 minutes or less, and particularly preferably 10 g / 10 minutes or less. On the other hand, it is preferably 1.0 g / 10 minutes or more, more preferably 2.0 g / 10 minutes or more. The MFR of the aliphatic-aromatic polyester resin (A) can be adjusted by the molecular weight.

[0053] [Method of manufacturing aliphatic-aromatic polyester] The method for producing the aliphatic-aromatic polyester is not particularly limited, and a known method such as the method disclosed in International Publication No. 2022 / 014434 can be adopted. Hereinafter, the method for producing the aliphatic-aromatic polyester will be described, but it is merely an example, and the method for producing the aliphatic-aromatic polyester is not limited to this embodiment. The polycondensation reaction at this time can be performed under suitable conditions that have been conventionally used, and is not particularly limited. Usually, a method is used in which the degree of polymerization is further increased by carrying out a decompression operation after the esterification and / or transesterification reaction has progressed.

[0054] When producing an aliphatic-aromatic polyester resin, the amounts of the diol component, the dicarboxylic acid component, and any other copolymerization components used are set so that the aliphatic-aromatic polyester resin produced has a desired composition. Usually, the diol component and the dicarboxylic acid component react in substantially equimolar amounts, but the diol component is usually used in an amount of 1 to 20 mol % in excess of the dicarboxylic acid component because it is distilled off during the esterification or transesterification reaction.

[0055] The reaction temperature for the esterification or transesterification reaction is not particularly limited as long as it is a temperature at which the esterification reaction can be carried out, but from the viewpoint of increasing the reaction rate, it is preferably 200°C or higher, and more preferably 210°C or higher, and in order to prevent discoloration of the polyester, it is preferably 270°C or lower, more preferably 260°C or lower, and particularly preferably 250°C or lower.

[0056] The reaction time for the esterification or transesterification reaction is not particularly limited, but is preferably 1 hour or more, and is preferably 10 hours or less, and more preferably 4 hours or less.

[0057] The reaction vessel is then depressurized to increase the degree of polymerization.

[0058] The reaction pressure for the polymerization reaction is not particularly limited, but is usually 0.01 kPa or more, preferably 0.03 kPa or more, and usually 1.4 kPa or less, preferably 0.4 kPa or less. If the pressure during the polycondensation reaction is too high, the polycondensation time becomes long, which leads to a decrease in molecular weight and coloration due to thermal decomposition of the polyester, and it tends to become difficult to produce a polyester that exhibits sufficient properties for practical use.

[0059] The reaction temperature for the polymerization reaction is not particularly limited, but is usually 215°C or higher, preferably 220°C or higher, and usually 270°C or lower, preferably 260°C or lower. If the reaction temperature is below the lower limit of the above range, the polycondensation reaction rate is slow, and not only does it take a long time to produce a polyester with a high degree of polymerization, but it also requires a high-power stirrer, which is economically disadvantageous. On the other hand, if the reaction temperature exceeds the upper limit of the above range, the polyester resin is likely to be thermally decomposed during production, and it tends to be difficult to produce a polyester with a high degree of polymerization.

[0060] The reaction time for the polymerization reaction is not particularly limited, but is usually 1 hour or more, and usually 15 hours or less, preferably 10 hours or less, and more preferably 8 hours or less. If the reaction time is too short, the reaction is insufficient, making it difficult to obtain a polyester with a high degree of polymerization, and the mechanical properties of the molded product tend to be poor. On the other hand, if the reaction time is too long, the molecular weight reduction due to thermal decomposition of the polyester resin becomes significant, and not only does the mechanical properties of the molded product tend to be poor, but the amount of carboxyl group terminals, which adversely affect the durability of the polyester resin, may increase due to thermal decomposition.

[0061] By controlling the temperature, time and reaction pressure of the polycondensation reaction within the above ranges, a polyester resin having a desired intrinsic viscosity can be obtained.

[0062] (Reaction catalyst) The aliphatic-aromatic polyester resin is usually produced in the presence of a catalyst. The catalyst may be selected from among known catalysts that can be used in the production of polyester resins, as long as the effects of the present invention are not significantly impaired.

[0063] As the catalyst, a compound containing at least one of metal elements of Groups 1 to 14 of the periodic table is generally used. In order to reduce the polyester end concentration that affects the thermal stability of the polyester, metal elements of Groups 3 to 6 of the periodic table that exhibit Lewis acidity are more preferred. Specific examples of the metal element include scandium, titanium, zirconium, vanadium, molybdenum, and tungsten, and titanium and zirconium are particularly preferred because of their availability, and titanium is further preferred because of its reaction activity.

[0064] In the present embodiment, as the catalyst, a compound containing an organic group, such as a carboxylate, an alkoxy salt, an organic sulfonate, or a β-diketonate salt, containing the above-mentioned metal element; or an inorganic compound, such as an oxide or a halide of the above-mentioned metal element, or a mixture thereof, is preferably used.

[0065] In this embodiment, the catalyst is preferably a compound that is liquid during polymerization or dissolves in an ester oligomer or polyester, because the polymerization rate increases when the catalyst is in a molten or dissolved state during polymerization. In addition, it is preferable to carry out polycondensation without a solvent, but a small amount of solvent may be used separately to dissolve the catalyst. Examples of the solvent for dissolving the catalyst include alcohols such as methanol, ethanol, isopropanol, or butanol, the above-mentioned diols such as ethylene glycol, butanediol, or pentanediol, ethers such as diethyl ether or tetrahydrofuran, nitriles such as acetonitrile, hydrocarbon compounds such as heptane or toluene, water, or mixtures thereof. In order to dissolve the catalyst, the catalyst can be diluted with diols such as 1,4-butanediol or ethylene glycol, and in this case, the diols can also function as raw materials for polyester.

[0066] The titanium compound is preferably a tetraalkyl titanate or a hydrolyzate thereof, specifically, tetra-n-propyl titanate, tetraisopropyl titanate, tetra- Examples of the titanate include n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, mixed titanates thereof, and hydrolysates thereof.

[0067] In addition, titanium compounds include alcohols, long-form periodic table (Nomenclature of Inorganic Chemistry IUPAC Recommendation A liquid obtained by mixing a Group 2 metal compound in the Periodic Table (hereinafter sometimes referred to as a Group 2 metal compound in the long-form periodic table) of the cations 2005), a phosphate ester compound, or a titanium compound may also be used.

[0068] The amount of catalyst added is not particularly limited, but the lower limit of the amount of metal relative to the polyester produced is usually 0.1 mass ppm or more, preferably 0.5 mass ppm or more, more preferably 1 mass ppm or more, and the upper limit is usually 3000 mass ppm or less, preferably 1000 mass ppm or less, more preferably 250 mass ppm or less, and particularly preferably 130 mass ppm or less. This range can be particularly preferably applied when a metal compound is used as a polycondensation catalyst. If the amount of catalyst used is too large, not only is it economically disadvantageous, but the carboxyl group terminal concentration of the polyester resin may increase, and the thermal stability and hydrolysis resistance of the polyester may decrease due to the increase in the amount of carboxyl group terminals and the residual catalyst concentration. Conversely, if the amount is too small, the polymerization activity decreases, which induces thermal decomposition of the polyester during polyester production, making it difficult to obtain a polyester that exhibits practically useful physical properties.

[0069] [Other ingredients] The resin composition may contain components (other components) other than the above-mentioned aliphatic-aromatic polyesters, and examples of such components include polyesters other than the above-mentioned aliphatic-aromatic polyesters; resins other than polyesters, such as polyamides, polyvinyl alcohols, or cellulose esters; carbodiimide compounds; isocyanate compounds; various additives, such as lubricants, fillers, plasticizers, antistatic agents, antioxidants, light stabilizers, UV absorbers, dyes, pigments, hydrolysis inhibitors, known surface wetting improvers, flame retardants, release agents, incineration aids, pigments, dispersing aids, surfactants, crystal nucleating agents, or compatibilizers; fine powders of animal / plant substances, such as starch, cellulose, paper, wood flour, chitin / chitosan, coconut shell powder, or walnut shell powder; or mixtures thereof. The other components can be used arbitrarily as long as they do not impair the effects of the present invention. These may be used alone or in combination of two or more, but it is preferable that the other components include a filler and / or a lubricant. The total content of the other components in the resin composition is preferably 0.01% by mass or more and 80% by mass or less so as not to impair the physical properties of the resin composition.

[0070] (Aliphatic polyester) The resin composition may further contain a polyester other than the aliphatic-aromatic polyester from the viewpoint of obtaining suitable moldability and mechanical properties. As the polyester other than the aliphatic-aromatic polyester, it is preferable to contain an aliphatic polyester from the viewpoint of obtaining good biodegradability. In this specification, the aliphatic polyester is not an aliphatic-aromatic polyester, but a polyester containing aliphatic diol and aliphatic dicarboxylic acid units as main constituent units, or a polyester containing aliphatic oxycarboxylic acid units as main constituent units.

[0071] In the polyester containing an aliphatic diol and an aliphatic dicarboxylic acid unit as the main constituent unit, the aliphatic diol that gives the diol unit is not particularly limited, but from the viewpoint of moldability and mechanical strength, an aliphatic diol having 2 to 10 carbon atoms is preferable, and an aliphatic diol having 4 to 6 carbon atoms is particularly preferable. For example, ethylene glycol, 1,3-propanediol, Among them, 1,4-butanediol is particularly preferable. The aliphatic diol may be used alone or in combination of two or more.

[0072] The aliphatic dicarboxylic acid that gives the aliphatic dicarboxylic acid unit contained in the polyester containing an aliphatic diol and an aliphatic dicarboxylic acid unit as the main constituent unit is not particularly limited, but is preferably a compound in which two carboxyl groups are bonded to a linear or branched aliphatic hydrocarbon group having 2 to 40 carbon atoms, specifically succinic acid, adipic acid, azelaic acid, sebacic acid, brassylic acid, suberic acid, dimer acid, etc. In particular, from the viewpoint of achieving both biodegradability and moldability, the aliphatic polyester preferably contains one or more aliphatic dicarboxylic acid units selected from the group consisting of succinic acid units, adipic acid units, azelaic acid units, sebacic acid units, and brassylic acid units as constituent units, and more preferably contains one or more aliphatic dicarboxylic acid units selected from the group consisting of succinic acid units, adipic acid units, and sebacic acid units as constituent units.

[0073] In addition, polyesters containing aliphatic diol and aliphatic dicarboxylic acid units as main constituent units may have repeating units derived from aliphatic oxycarboxylic acids. Specific examples of aliphatic oxycarboxylic acid components that impart aliphatic oxycarboxylic acid units include, for example, lactic acid, glycolic acid, 2-hydroxy-n-butyric acid, 2-hydroxycaproic acid, 6-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, and the like, or derivatives thereof such as lower alkyl esters or intramolecular esters. When optical isomers exist in these, they may be any of D-form, L-form, or racemic form, and may be in the form of solid, liquid, or aqueous solution. Among these, lactic acid or glycolic acid, or derivatives thereof, are particularly preferred. These aliphatic oxycarboxylic acids may be used alone or as a mixture of two or more.

[0074] When the polyester containing an aliphatic diol and an aliphatic dicarboxylic acid unit as the main structural unit contains these aliphatic oxycarboxylic acid units, the content thereof is preferably 10 mol % or less, more preferably 5 mol % or less, even more preferably 2 mol % or less, and most preferably 0 mol % (not contained or below the detection limit), based on 100 mol % of all structural units constituting the aliphatic polyester, from the viewpoint of moldability.

[0075] In addition, the polyester containing an aliphatic diol and an aliphatic dicarboxylic acid unit as a main constituent unit may have an increased melt viscosity by copolymerizing a trifunctional or higher aliphatic polyhydric alcohol, a trifunctional or higher aliphatic polycarboxylic acid or an acid anhydride thereof, or a trifunctional or higher aliphatic polyoxycarboxylic acid component.

[0076] Specific examples of trifunctional aliphatic polyhydric alcohols include trimethylolpropane, glycerin, etc., and specific examples of tetrafunctional aliphatic polyhydric alcohols include pentaerythritol, etc. These may be used alone or in combination of two or more.

[0077] A specific example of a trifunctional aliphatic polycarboxylic acid or its anhydride is propanetricarboxylic acid or its anhydride, and a specific example of a tetrafunctional polycarboxylic acid or its anhydride is cyclopentanetetracarboxylic acid or its anhydride, etc. These may be used alone or in combination of two or more.

[0078] In addition, trifunctional aliphatic oxycarboxylic acids are divided into (i) a type having two carboxyl groups and one hydroxyl group in the same molecule, and (ii) a type having one carboxyl group and two hydroxyl groups. Either type can be used, but the moldability, mechanical strength, and From the viewpoint of the appearance of the molded product, (i) a type having two carboxyl groups and one hydroxyl group in the same molecule, such as malic acid, is preferred, and more specifically, malic acid is preferably used. In addition, the tetrafunctional aliphatic oxycarboxylic acid component is divided into (i) a type having three carboxyl groups and one hydroxyl group in the same molecule, (ii) a type having two carboxyl groups and two hydroxyl groups in the same molecule, and (iii) a type having three hydroxyl groups and one carboxyl group in the same molecule, and any type can be used, but those having multiple carboxyl groups are preferred, and more specifically, citric acid, tartaric acid, etc. can be mentioned. These can be used alone or in a mixture of two or more types.

[0079] When the polyester containing aliphatic diol and aliphatic dicarboxylic acid units as main constituent units contains such constituent units derived from trifunctional or higher components, the content thereof is usually 0 mol% or more, preferably 0.01 mol% or more, and usually 5 mol% or less, preferably 2.5 mol% or less, based on 100 mol% of all constituent units constituting the aliphatic polyester. 1 It can be determined from the integral value obtained by H-NMR measurement.

[0080] The method for producing the aliphatic polyester can be a known method for producing polyester. The polycondensation reaction can be set under suitable conditions that have been used in the past, and is not particularly limited. Usually, a method is used in which the degree of polymerization is further increased by carrying out a decompression operation after the esterification reaction has progressed.

[0081] The molecular weight of the aliphatic polyester is not particularly limited, but can be measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the aliphatic polyester, using monodisperse polystyrene as the standard substance, is usually 10,000 or more and 1,000,000 or less. However, because this is advantageous in terms of moldability and mechanical strength, it is preferably 20,000 or more and 500,000 or less, and more preferably 50,000 or more and 400,000 or less.

[0082] The melt flow rate (MFR) of an aliphatic polyester is a value measured at 190°C under a load of 2.16 kg according to JIS K7210 (2014), and is usually 0.1 g / 10 min or more and 100 g / 10 min or less, but from the viewpoint of moldability and mechanical strength, it is preferably 50 g / 10 min or less, and particularly preferably 30 g / 10 min or less. The MFR of an aliphatic polyester can be adjusted by the molecular weight.

[0083] The melting point of the aliphatic polyester is preferably 70° C. or higher, more preferably 75° C. or higher, and is preferably 200° C. or lower, more preferably 190° C. or lower, and particularly preferably lower than 180° C. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range. The method for measuring the melting point is not particularly limited, but it can be measured using a differential scanning calorimeter (manufactured by Seiko Corporation, product name: DSC220). The elastic modulus of the aliphatic polyester is preferably 180 to 2500 MPa. If the melting point is outside the above range, the moldability is poor, and if the elastic modulus is less than 180 MPa, problems are likely to occur in the molding processability, while if the elastic modulus exceeds 2500 MPa, the obtained film tends to be brittle.

[0084] The method of adjusting the melting point and elastic modulus of the aliphatic polyester is not particularly limited, but for example, in a polyester containing an aliphatic diol and an aliphatic dicarboxylic acid unit as a main constituent unit, it is possible to adjust by adjusting the type of copolymerization component of the aliphatic dicarboxylic acid component other than succinic acid and the copolymerization ratio thereof. Also, for example, in a polyester containing an aliphatic oxycarboxylic acid unit as a main constituent unit, it is possible to adjust by adjusting the copolymerization ratio of the aliphatic oxycarboxylic acid component or the optical isomer ratio of the aliphatic oxycarboxylic acid component.

[0085] Specific examples of aliphatic polyesters include polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene succinate sebacate (PBSSe), polycaprolactone (PCL), poly(3-hydroxybutyrate) (PHB), poly(3-hydroxybutyrate / 3-hydroxyvalerate) (PHBV), poly(3-hydroxybutyrate / 3-hydroxyhexyl) (PHBV), and poly(3-hydroxybutyrate / 3-hydroxyhexyl) (PHBV). Examples of suitable polybutylene succinate include polybutylene succinate adipate, polybutylene succinate sebacate, poly(3-hydroxybutyrate / 3-hydroxyhexanoate) (PHBH), and polylactic acid (PLA). From the viewpoints of heat resistance, moldability, biodegradability, and the like, preferred are polybutylene succinate, polybutylene succinate adipate, polybutylene succinate sebacate, poly(3-hydroxybutyrate / 3-hydroxyhexanoate), and polylactic acid, and more preferred are polybutylene succinate, polybutylene succinate sebacate, and polylactic acid.

[0086] As the aliphatic polyester, commercially available products can be used, such as "BioPBS (registered trademark) FZ71PB," "BioPBS (registered trademark) FZ71PM," "BioPBS (registered trademark) FZ91PB," "BioPBS (registered trademark) FZ91PM," "BioPBS (registered trademark) FD92PB," and "BioPBS (registered trademark) FD92PM," all manufactured by PTTMCC Biochem.

[0087] The aliphatic polyester is not limited to one type, and two or more types of aliphatic polyesters differing in the types and ratios of constituent units, production methods, physical properties, etc. may be blended and used.

[0088] When the resin composition contains an aliphatic polyester, the mixing ratio of the aliphatic polyester is preferably 80 parts by mass or less, more preferably 75 parts by mass or less, per 100 parts by mass of the total of the aliphatic-aromatic polyester and the aliphatic polyester. When the content ratio of the aliphatic polyester is equal to or less than the above upper limit, good film elongation and tear strength are realized.

[0089] The bio-based carbon content of the aliphatic polyester as measured by ISO 16620-2 is not particularly limited, but from the viewpoint of suppressing carbon dioxide emissions, it is preferably 20% or more, more preferably 35% or more, and even more preferably 50% or more, and there is no particular need to set an upper limit, and it may be 100% or less, 80% or less, 70% or less, or 60% or less. The bio-based carbon content is calculated based on the total carbon mass of carbon 14( 14 C) from the bio-based carbon content and polymerization ratio of each of the raw materials, the aliphatic diol component, the aliphatic dicarboxylic acid component, and the aromatic dicarboxylic acid component.

[0090] (lubricant) The resin composition may contain a lubricant. When the resin composition contains a lubricant, the opening property of the film made of the resin composition can be improved, and the processability when the film is molded into a bag can be improved.

[0091] The lubricant may be any known lubricant without any particular limitation. Specifically, paraffins such as paraffin oil or solid paraffin; higher fatty acids such as stearic acid or palmitic acid; higher alcohols such as palmityl alcohol or stearyl alcohol; metal salts of fatty acids such as calcium stearate, zinc stearate, barium stearate, aluminum stearate, magnesium stearate, or sodium palmitate; fatty acid esters such as butyl stearate, glycerin monostearate, or diethylene glycol monostearate; stearamide, methylene bis(glycerol) stearate, or the like; Examples of the lubricant include fatty acid amides such as stearamide, ethylene bisstearamide, ethylene diamide of oxystearic acid, methylol amide, oleyl amide, stearic acid amide, and erucic acid amide; and waxes such as carnauba wax and montan wax. The lubricant may be used alone or in any combination of two or more kinds in any ratio. Among these, erucic acid amide is particularly preferred. When the resin composition contains a lubricant, it is usually used in an amount of 0.01 to 2% by mass, and preferably 0.05 to 0.5% by mass in the resin composition. When the content of the lubricant is equal to or more than the above lower limit, the effect of the lubricant can be sufficiently obtained, and when the content is equal to or less than the above upper limit, excessive slippage of the film can be prevented, resulting in a film with excellent secondary processability.

[0092] (Filler) The resin composition may contain a filler. When the resin composition contains a filler, the crystallization rate of the resin composition is improved, which contributes to stabilization during film molding and reduction of anisotropy of the mechanical properties of the film. In addition, blocking between films may be prevented, and the gas barrier properties of the film can be improved and rigidity can be imparted. In addition, light shielding properties and light reflectivity can be improved.

[0093] Depending on the shape, the filler may be fibrous, powdery, plate-like, or needle-like, and powdery or plate-like fillers are particularly preferred. Examples of powdery fillers include mineral particles such as zeolite, diatomaceous earth, kaolin, silica, or quartz powder; metal carbonate particles such as calcium carbonate, magnesium carbonate, or heavy calcium carbonate; metal silicate particles such as calcium silicate, aluminum silicate, or magnesium silicate; metal oxide particles such as alumina, silica, zinc oxide, titanium oxide, or aluminosilicate; metal hydroxide particles such as aluminum hydroxide, calcium hydroxide, or magnesium hydroxide; metal sulfate particles such as barium sulfate or calcium sulfate; or carbon particles such as carbon black. Examples of plate-like fillers include talc, clay, or mica.

[0094] From the viewpoint of preventing blocking, talc, calcium carbonate, or silica is preferred, and from the viewpoint of coloring the film and improving the light-shielding property or light reflectance, carbon black or titanium oxide is preferred.

[0095] Although there is no particular limitation on the average particle size of the filler used, the average particle size is preferably 0.5 μm or more, more preferably 0.6 μm or more, and even more preferably 0.7 μm or more, from the viewpoint of improving the film physical properties and handling, and from the viewpoint of preventing the film from having poor appearance or breaking, the average particle size is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less.

[0096] When a needle-like filler is used, the upper limit of the average aspect ratio is usually 1000 or less, preferably 500 or less, more preferably 100 or less, and the lower limit is usually 1 or more, preferably 10 or more, more preferably 15 or more. If the aspect ratio is too small, the expected physical properties such as rigidity and heat resistance tend not to be exhibited, and if it is too large, it tends to cause poor appearance and deteriorate the physical properties of the film. The aspect ratio here is the ratio of the long diameter to the short diameter of the filler. The aspect ratio of a particle is the arithmetic average value of the ratio of the longest diameter to the shortest diameter of at least 10 particles observed in a scanning electron microscope photograph with a field of view of 100 μm × 100 μm.

[0097] There is no particular limitation on the method for measuring the volume average particle size, but the particles dispersed in a dispersion medium can be measured by a sedimentation method, by laser scattering analysis, or by a laser Doppler method.

[0098] There is no particular restriction on the average specific surface area of ​​the filler used, but if the specific surface area is too large, the rigidity tends not to be sufficiently improved, and if it is too small, the transparency tends to decrease. The specific surface area of ​​the filler used is usually 8000 cm 2 / g or more, preferably 10000cm 2 / g or more, while usually 50000cm 2 / g or less, preferably 40000 cm 2 / g or less.

[0099] As the compound used as the filler, talc, calcium carbonate, silica, aluminosilicate, titanium oxide, barium sulfate, etc. can be preferably used, and talc, calcium carbonate, or silica is more preferably used in consideration of the environment after biodegradation. Specifically, talc includes LMS100, LMR100, PKP80, PKP53S, MG115, SG95 manufactured by Fuji Talc Kogyo, or K-1 manufactured by Nippon Talc Co., Ltd. Examples of calcium carbonate include NITOREX30P, NITOREX23P, NS#100 manufactured by Nitto Funka, NITOREX30PS, NCC#2310, NCC#1010, NCC-V2300, NCC-V1000 of the NCC series, or Whiscal A manufactured by Maruo Calcium Co., Ltd. Examples of silica include Aerosil 200 and Aerosil 300 manufactured by Nippon Aerosil Co., Ltd. As titanium oxide, CR-60, CR-80, and CR-68 manufactured by Ishihara Sangyo Kaisha can be used.

[0100] The filler may be surface-treated, and in this case, it may be possible to improve the dispersibility of the filler, improve the flowability of the resin composition, and improve the smoothness and opening property of the film. Furthermore, by performing surface treatment, it is expected that the required amount of additives such as filler and plasticizer to be mixed in the resin composition can be reduced. The surface treatment of the filler can be performed by a commonly known method, and the method of surface treatment is not particularly limited. Examples of the surface treatment agent include linear fatty acids having 6 to 40 carbon atoms, branched fatty acids, and ester compounds thereof.

[0101] These fillers may be used alone or in combination of two or more different fillers having different materials, physical properties, surface treatments, etc.

[0102] When the resin composition contains a filler, the filler is used in the range of 0.05 to 40% by mass in the resin composition. If the content of the filler is equal to or more than the lower limit, the effect of the filler can be sufficiently obtained, and if the content is equal to or less than the upper limit, deterioration of physical properties due to poor dispersion of the filler can be prevented.

[0103] (Plasticizer) The resin composition may contain a plasticizer. When the resin composition contains a plasticizer, the viscosity of the resin composition before molding increases, which makes it easier to improve the deterioration of the flowability of the resin composition.

[0104] As the plasticizer, any known plasticizer can be used without any particular limitation. For example, fatty acid esters such as methyl adipate, diethyl adipate, diisopropyl adipate, di-n-propyl adipate, di-2-ethylhexyl adipate, diisobutyl adipate, dibutyl adipate, diisodecyl adipate, dibutyl diglycol adipate, di-2-ethylhexyl azelate, dibutyl sebacate, di-2-ethylhexyl sebacate, methyl acetyl lysylate, or epoxidized soybean oil; glycerin esters such as triacetin; maleic and fumaric acid esters such as diethyl maleate, dibutyl maleate, dioctyl maleate, dibutyl fumarate, or dioctyl fumarate; polyesters such as 1,3-butylene glycol adipate; epoxidized esters; trimellitic acid esters such as trioctyl trimellitate; triethylene glycol diacetate; citric acid such as tributyl acetyl citrate or triethyl citrate. Examples of the plasticizer include esters, acetylated monoglycerides such as glycerin diacetomonopropionate, glycerin diacetomonocaprylate, glycerin diacetomonocaprate, glycerin diacetomonolaurate, glycerin diacetomonooleate, glycerin monoacetomonobehenate, and glycerin monoacetomonostearate, polyglycerin fatty acid esters such as diglycerin acetate, decaglycerin propionate, tetraglycerin caprylate, decaglycerin laurate, decaglycerin oleate, and decaglycerin behenate, and rosin derivatives. These plasticizers may be used alone or in combination of two or more.

[0105] When the resin composition contains a plasticizer, the plasticizer is usually used in the range of 0.05 to 10 mass % in the resin composition. If the content of the plasticizer is equal to or more than the lower limit, the effect of improving the fluidity by the plasticizer can be sufficiently obtained, and if the content is equal to or less than the upper limit, the fluidity can be improved without problems such as bleeding out of the plasticizer.

[0106] (Antistatic agent) The resin composition may contain an antistatic agent. When the resin composition contains an antistatic agent, the moldability of the film made of the resin composition when it is molded into a bag can be improved in some cases.

[0107] As the antistatic agent, any agent can be used as long as it does not significantly impair the effects of the present invention. Specific examples of the antistatic agent include nonionic, cationic, and anionic surfactants.

[0108] Examples of nonionic antistatic agents include glycerin fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, alkyldiethanolamines, hydroxyalkylmonoethanolamines, polyoxyethylene alkylamines, polyoxyethylene alkylamine fatty acid esters, alkyldiethanolamides, etc. Among these, alkyldiethanolamines, etc. are preferred. Examples of the cationic antistatic agent include tetraalkylammonium salts and trialkylbenzylammonium salts. Examples of anionic antistatic agents include alkyl sulfonates, alkyl benzene sulfonates, and alkyl phosphates. Among these, alkyl benzene sulfonates are preferred because they have good kneadability with resins and a high antistatic effect.

[0109] When the resin composition contains an antistatic agent, the amount of the antistatic agent used is arbitrary as long as it does not significantly impair the effects of the present invention, but is usually 0.5% by mass or more, preferably 1% by mass or more, and usually 5% by mass or less, preferably 3% by mass or less in the resin composition. If the amount exceeds the above range, the surface of the film made of the resin composition tends to become sticky, and the product value tends to decrease. If the amount is below the above range, the antistatic effect tends to decrease.

[0110] (starch) The resin composition may contain starch. When the resin composition contains starch, the biodegradability and bio-based carbon content of the resin composition can be improved. Specific examples of starch include corn starch, waxy corn starch, high amylose corn starch, wheat starch, rice starch, potato starch, sweet potato starch, tapioca starch, sago starch, bracken starch, pea starch, and derivatives thereof. Only one of these may be used, or two or more of them may be used. In addition, either unmodified or modified products may be used. Here, modification includes any method of modification, such as chemical, physical, or biological, and chemical modification includes esterification, etherification, oxidation, reduction, coupling, dehydration, hydrolysis, dehydrogenation, or halogenation of part or all of the structural units of carbohydrates (polysaccharides). Modification refers to modification by chemical reactions such as genation, and in particular etherification or esterification of hydroxyl groups. Physical modification refers to changing physical properties such as imparting plasticity with glycerin, water, inorganic salts, etc. Biological modification refers to changing chemical structures, etc. using living organisms.

[0111] When the resin composition contains starch, the starch is used in the range of 1 to 60 mass % in the resin composition. When the content of starch is equal to or more than the lower limit, the effect of containing starch can be sufficiently obtained, and when the content is equal to or less than the upper limit, the effect of the present invention can be efficiently exhibited without causing an extreme increase in viscosity.

[0112] (Light stabilizer) The resin composition may contain a light stabilizer. Examples of light stabilizers include decanedioic acid bis(2,2,6,6-tetramethyl-1(octyloxy)-4-piperidinyl) ester, reaction product of 1,1-dimethylethyl hydroperoxide with octane, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate, and bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate. Examples of such stabilizers include hindered amine stabilizers such as bacate, 1-[2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl]-4-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]-2,2,6,6-tetramethylpiperidine, and poly[[6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidyl)imino]hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}]. The light fastener is preferably used in combination with an ultraviolet absorber, and a combination of a hindered amine stabilizer and an ultraviolet absorber is effective.

[0113] When the resin composition contains a light stabilizer, the amount of the light stabilizer used is usually 100 ppm by mass or more, preferably 200 ppm by mass or more, and usually 5% by mass or less, preferably 1% by mass or less, more preferably 0.5% by mass or less, based on the mass of the resin composition. If the amount is less than this range, the effect of the light stabilizer tends to be small. If the amount is more than this range, the rigidity and tear resistance tend to be reduced, and the heat resistance of the resin composition tends to be poor, and the light stabilizer tends to bleed out.

[0114] (UV absorber) The resin composition may contain an ultraviolet absorbing agent. Examples of the ultraviolet absorbent include 2-(2H-benzotriazol-2-yl)-4-6-bis(1-methyl-1-phenylethyl)phenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]phenol, etc. It is particularly preferable to use two or more different types of ultraviolet absorbents in combination.

[0115] When the resin composition contains an ultraviolet absorber, the amount of the ultraviolet absorber is optional as long as it does not significantly impair the effects of the present invention, but is usually 100 mass ppm or more, preferably 200 mass ppm or more, and usually 5 mass% or less, preferably 2 mass% or less, more preferably 0.5 mass% or less, based on the mass of the resin composition. If it is below this range, the effect of the ultraviolet absorber tends to decrease. Also, if it exceeds this range, the production cost tends to be too high, the heat resistance of the resin composition tends to be poor, and the ultraviolet absorber tends to bleed out.

[0116] (Heat stabilizer) The resin composition may contain a heat stabilizer. Heat stabilizers include dibutylhydroxytoluene (BHT; 2,6-di-t-butyl-4-methylphenol), 2,2'-methylenebis(4-methyl-6-t-butylphenol), pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 3,3',3”,5,5',5”-hexa-tert-butyl-a,a',a”-(mesitylene-2,4,6-triyl)tri-p-cresol, and octadecyl-3-(3,5-di-tert-butyl -4-hydroxyphenyl)propionate, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylyl)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, calcium diethyl bis[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, bis( Hindered phenolic heat stabilizers such as 2,2'-dihydroxy-3,3'-di-tert-butyl-5,5'-dimethylphenyl)ethane or N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide; tridecyl phosphite, diphenyl decyl phosphite, tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphonite, bis[2,4-bis(1,1-dimethylethyl )-6-methylphenyl]ethyl ester phosphorous acid, or bis(2,4-di-tert-butylphenyl)pentaerythritol diphasphite, or other phosphorus-based heat stabilizers; lactone-based heat stabilizers such as the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and xylene; or sulfur-based antioxidants such as dilauryl thiodipropionate or distearyl thiodipropionate; etc. These heat stabilizers may be used alone or in combination of two or more.

[0117] When the resin composition contains a heat stabilizer, the amount of the heat stabilizer is usually 100 mass ppm or more, preferably 200 mass ppm or more, and usually 5 mass % or less, preferably 1 mass % or less, more preferably 0.5 mass % or less, based on the mass of the resin composition. If it is below this range, the effect of the heat stabilizer tends to be reduced. On the other hand, if it exceeds this range, the production cost tends to be high, and the heat stabilizer may bleed out.

[0118] (End-capping agent) The resin composition may contain an end-capping agent mainly for the purpose of suppressing hydrolysis caused by moisture in the atmosphere. Examples of the terminal blocking agent include carbodiimide compounds, epoxy compounds, and oxazoline compounds. Among the carbodiimide compounds, examples of monocarbodiimide compounds include dicyclohexylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, t-butylisopropylcarbodiimide, diphenylcarbodiimide, di-t-butylcarbodiimide, and di-β-naphthylcarbodiimide. Among these, dicyclohexylcarbodiimide and diisopropylcarbodiimide are preferred. Furthermore, as the polycarbodiimide compound, for example, those produced by the methods described in U.S. Pat. No. 2,941,956, Japanese Patent Publication No. 47-33279, J. Org. Chem., Vol. 28, pp. 2069-2075 (1963), and Chemical Review 1981, Vol. 81, No. 4, pp. 619-621, etc., can be used. However, when using a compound that undergoes crosslinking or chain extension, such as polycarbodiimide, it is necessary to use it within a range that does not impair moldability due to an increase in viscosity. These end-capping agents may be used alone or in combination of two or more.

[0119] When the resin composition contains a terminal blocking agent, the amount of the terminal blocking agent used is usually 0.1 to 5% by mass based on the resin composition. If the amount is less than this range, the effect of the terminal blocking agent cannot be obtained sufficiently, whereas if the amount is more than this range, the crosslinking reaction may proceed excessively, causing gelation.

[0120] <Film manufacturing method> The method for producing the film is not particularly limited as long as it includes a step of performing a stretching treatment, and the film can be produced by a known polyester molding method or by combining known molding methods. For example, known methods can be used, such as a method of simultaneously performing molding and stretching by inflation molding or T-die molding, or a method of further performing a stretching process such as uniaxial stretching, sequential biaxial stretching, or simultaneous biaxial stretching on a film or sheet molded by inflation molding, T-die molding, calendar molding, compression molding, or the like. Moreover, these molding methods may be single-layer molding or multi-layer molding. A preferred embodiment of the film production method will be described below, but the present invention is not limited to this method.

[0121] A film manufacturing method according to another embodiment of the present invention (also simply referred to as a "film manufacturing method") includes the following steps: The method includes a molding step of extruding the resin composition containing the aliphatic-aromatic polyester through a die lip and performing inflation molding to obtain a film, In the molding step, the gap d (mm) of the die lip, the blow ratio B, and the thickness t (mm) of the molded film satisfy the following formula (1): A method for producing a film. d / (B 2 ×t)≧3 (1) The method for producing the film may include steps other than the above-mentioned forming step.

[0122] [Preparation process] The method for producing the film may include a preparation step of preparing a resin composition containing an aliphatic-aromatic polyester before the molding step described below. The method for preparing the resin composition is not particularly limited, and may be, for example, a method of mixing raw materials. The components contained in the resin composition include the aliphatic-aromatic polyester and the other optional components described above. In addition, the contents of each component in the resin composition can be the same as the contents of each component in the film described above.

[0123] [Molding process] The method for producing the film includes a molding step of extruding a resin composition through an annular die lip and carrying out inflation molding to obtain a film. The method for performing inflation molding is not particularly limited, and any known method can be used. The conditions for the molding are not particularly limited as long as the relational expression represented by the above-mentioned formula (1) is satisfied.

[0124] The extrusion method for performing inflation molding is not particularly limited as long as it can extrude the resin composition from a die, and can be performed using a known extruder. For example, an extruder having a single screw or a twin screw can be used.

[0125] When the die lip gap d (mm), the blow ratio B, and the thickness t (mm) of the film after molding satisfy the relational expression represented by the above formula (1), the anisotropy parameter AP obtained by measuring the polarized Raman spectrum of the film surface of the above-mentioned film is AP measured by the following evaluation method. max and AP оrg The ratio AP expressed as max / AP оrg However, it is easy to obtain a film that falls within the desired ranges described in the description of the film embodiments above. It becomes. (Evaluation method) In a microscopic laser Raman spectrometer, a linearly polarized laser beam with a wavelength of 633 nm, in which a 1 / 2 λ plate is inserted to set the direction of polarization (direction of vibration of the electric field) at an arbitrary angle, is made to enter the film surface perpendicularly, and the spectrum of the generated Raman scattered light is measured. -1 The area of ​​the Raman band with a peak near I 1612 and 2850 cm, which corresponds to the stretching vibration of the methylene group in the polymer chain. -1 The area of ​​the Raman band with a peak near I 2850 In this case, among the directions of the arbitrary angle, I 1612 / I 2850 The anisotropy parameter measured in the direction where the ratio is maximum is AP max and the anisotropy parameter measured in the direction perpendicular to the direction is AP оrg Let us assume that.

[0126] The die lip gap d (mm) may be set arbitrarily so long as it satisfies the relational expression represented by the above formula (1); from the viewpoint of preventing decomposition of the resin due to shear heat and excessive load on the extruder, it is usually 0.3 mm or more, preferably 0.4 mm or more, more preferably 0.6 mm or more, even more preferably 0.8 mm or more, and particularly preferably 1.0 mm or more; and from the viewpoint of improving bubble stability and mouth opening properties by increasing cooling efficiency, it is usually 5.0 mm or less, preferably 4.0 mm or less, more preferably 3.0 mm or less, even more preferably 2.5 mm or less, and particularly preferably 2.0 mm or less.

[0127] The blow ratio B may be set arbitrarily so long as it satisfies the relational expression represented by the above formula (1); from the viewpoint of increasing the mechanical strength by stretching, it is usually 1.2 or more, preferably 1.4 or more, more preferably 1.6 or more, even more preferably 1.8 or more, and particularly preferably 2 or more; and from the viewpoint of making it easier to tear in one direction, it is usually 4 or less, preferably 3.8 mm or less, more preferably 3.5 or less, even more preferably 3.3 or less, and particularly preferably 3 or less. The blow ratio B is the ratio of the diameter D' of the expanded cylindrical film to the diameter D of the annular die lip (D' / D).

[0128] The thickness t (mm) of the molded film may be set arbitrarily so long as it satisfies the relational expression represented by the above formula (1); from the viewpoints of practical strength and ease of handling, it is usually 0.01 mm or more, preferably 0.015 mm or more, more preferably 0.02 mm or more, even more preferably 0.025 mm or more, and particularly preferably 0.03 mm or more; and from the viewpoint of biodegradability, it is usually 0.2 mm or less, preferably 0.15 mm or less, more preferably 0.1 mm or less, even more preferably 0.075 mm or less, and particularly preferably 0.05 mm or less.

[0129] The die temperature is not particularly limited and can be set appropriately depending on the composition of the resin composition; from the viewpoints of stable extrusion and smoothness of the film surface, the die temperature is preferably 120°C or higher, more preferably 130°C or higher, and even more preferably 140°C or higher; and from the viewpoints of bubble stability and mouth opening property, the die temperature is preferably 220°C or lower, more preferably 210°C or lower, and even more preferably 200°C or lower.

[0130] The tubular film obtained by inflation molding is cut, heat sealed, and otherwise processed into a desired shape, such as a rolled film or a bag.

[0131] As described above, the die lip gap d (mm), the blow ratio B, and the film thickness after molding When the thickness t (mm) of the max / AP оrg This makes it easier to obtain a film whose optical properties fall within the desired range. In addition to satisfying the relational expression represented by the above formula (1), the AP can be obtained by adjusting the type and amount of the resin other than the aliphatic-aromatic polyester and the filler in the resin composition. max / AP оrg For example, when the resin composition contains polylactic acid, the anisotropy parameter in the MD direction of the produced film tends to be large and the anisotropy parameter in the TD direction tends to be small, and thus the tear strength in the MD direction tends to be high and the tear strength in the TD direction tends to be low.

[0132] <Film characteristics> (Bio-based carbon content) The total bio-based carbon content of the resin composition measured by ISO 16620-2 is not particularly limited, but is preferably 20% or more, more preferably 35% or more, and even more preferably 50% or more, and there is no particular need to set an upper limit, and it may be 100%, 90% or less, 80% or less, or 70% or less. Increasing the bio-based carbon content can suppress fossil fuel consumption and reduce carbon dioxide emissions, which is beneficial from the perspective of protecting the global environment. The above bio-based carbon content does not have to be satisfied by the aliphatic-aromatic polyester alone, but may be satisfied by the entire resin composition. For example, the resin composition may contain an aliphatic-aromatic polyester with a bio-based carbon content of 0% and an aliphatic polyester with a bio-based carbon content of 49%, and the content of each component may be appropriately adjusted to fall within the above range. The above bio-based carbon content can be controlled by adjusting the ratio of monomer units produced from plant-derived raw materials to all structural units constituting one or more types of polyester contained in the resin composition. The bio-based carbon content above is calculated based on the carbon 14( 14 C). For example, when determining the bio-based carbon content of the polyester contained in the resin composition, it can also be determined by calculation from the bio-based carbon contents and polymerization ratios of the aliphatic diol component, the aliphatic dicarboxylic acid component, and the aromatic dicarboxylic acid component, which are the raw materials. In this specification, the term "biodegradable resin composition" generally refers to a resin composition having the above-mentioned bio-based carbon content of at least 10%.

[0133] (Tear strength) For the tear strength of the film measured based on ISO 6383-2, AP max The tear strength (N) in the direction in which the tear was measured divided by the film thickness (mm) (TR 1 From the viewpoint of ensuring sufficient strength, the strength is preferably 70 N / mm or more, more preferably 75 N / mm or more, even more preferably 80 N / mm or more, and particularly preferably 85 N / mm or more, and the upper limit is not particularly limited and may be, for example, 200 N / mm or less, 160 N / mm or less, or 120 N / mm or less. Also, AP оrg The tear strength (N) in the direction in which the tear was measured divided by the thickness (mm) of the film (TR 2 From the viewpoint of strength, it is preferably 2.5 N / mm or more, more preferably 3.5 N / mm or more, even more preferably 4.5 N / mm or more, and particularly preferably 6.0 N / mm or more. From the viewpoint of ease of tearing in one direction, it is preferably 20 N / mm or less, more preferably 15 N / mm or less, even more preferably 12 N / mm or less, and particularly preferably 10 N / mm or less. In terms of ease of tearing in one direction, AP оrg The tear strength in the direction in which the tear strength was measured is Divided by the film thickness (TR 2 ) is AP max The tear strength in the direction in which the tear was measured divided by the film thickness (TR 1 ), preferably 1 / 10 or less, more preferably 1 / 15 or less, even more preferably 1 / 20 or less, and particularly preferably 1 / 30 or less.

[0134] <Film Uses> The uses of the film are not particularly limited, and the film can be used, for example, as packaging material, wrap film, adhesive tape, decorative tape, packaging string, and the like. Among these, the film according to the present embodiment is preferably used as a packaging material, particularly an easy-open packaging material, because it has sufficient strength and is easily tearable in one direction. EXAMPLES

[0135] Hereinafter, specific aspects of the present invention will be described in more detail using examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention. Note that the values ​​of various manufacturing conditions and evaluation results in the following examples are meant as preferred upper or lower limit values ​​in the embodiments of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values ​​and the values ​​of the following examples or values ​​of the examples.

[0136] <Analysis, measurement and evaluation methods> [Bio-based carbon content] The bio-based carbon content of each polyester resin and resin composition was evaluated according to ISO 16620-2 and the methods described above in the explanations of the resin composition, aliphatic-aromatic polyester, and aliphatic polyester. The results are shown in Table 1. Specifically, the bio-based carbon content of the resin composition was measured by burning the resin composition, capturing the carbon dioxide, and reducing it with hydrogen and a catalyst to recover the carbon atoms in the composition as graphite. Next, the carbon isotope ratio was measured using an accelerator mass spectrometer. 14 The same proportion of carbon derived from biomass (bio-based carbon) is present due to the presence of C. 14 C is included. 14 Since C decays with a half-life of 5730 years, carbon derived from fossil resources has 14 Therefore, the standard concentration of C in the modern atmosphere is 14 C ratio in the sample 14 The biobased carbon content was calculated by calculating the proportion of C.

[0137] [Anisotropy Parameter] Using a microscopic laser Raman spectrometer (HR-800 manufactured by Horiba, Ltd.), linearly polarized laser light with a wavelength of 633 nm was incident perpendicularly on the surface of the produced film, with the direction of polarization (direction of vibration of the electric field) set to an arbitrary angle by inserting a 1 / 2λ plate into the laser light, and the spectrum of the generated Raman scattered light was measured. 1612 cm, which corresponds to the C=C stretching vibration of the benzene ring derived from the terephthalic acid unit -1 The area of ​​the Raman band with a peak near I 1612 and 2850 cm, which corresponds to the stretching vibration of the methylene group in the polymer chain. -1 The area of ​​the Raman band with a peak near I 2850 In this case, among the directions of the arbitrary angle, I 1612 / I 2850 The anisotropy parameter measured in the direction where the ratio is maximum is AP max and the anisotropy parameter measured in the direction perpendicular to the direction is AP оrg The obtained AP max and AP оrg From AP max / AP оrg The results are shown in Table 1. In addition, AP max and APоrg The polarization direction of each was either MD or TD. For the anisotropy parameters, five different measurement points were arbitrarily selected on the surface of one film, and the AP max / AP оrg After calculating the ratios, the average value of the three ratios excluding the minimum and maximum values ​​out of the five ratios calculated was evaluated.

[0138] [Tear strength] Using the produced film, test specimens were prepared in accordance with ISO 6383-2, and the tear strength (N) of the test specimens in MD and TD was measured. The tear strength divided by the thickness (mm) of the test specimen (N / mm) and the tear strength ratio (MD / TD) are shown in Table 1.

[0139] <Raw materials> Aliphatic-aromatic polyester 1 Polybutylene succinate terephthalate (PBST) synthesized by Production Example 1 described later (Bio-based carbon content: 22%, MFR (190°C, load 2.16 kg): 5g / 10min, Mw: 120,000, molar ratio of succinic acid unit to terephthalic acid unit = 55:45)

[0140] Aliphatic-aromatic polyester 2 Polybutylene adipate terephthalate (PBAT): BASF Ecoflex C1200" (Bio-based carbon content: 0%, MFR (190°C, load 2.16 kg): 5g / 10min, Mw: 120,000, molar ratio of adipic acid unit to terephthalic acid unit = 53:47)

[0141] Aliphatic polyester 1 Polybutylene succinate (PBS): "BioPBS FZ91PB" manufactured by PTT MCC Biochem (Bio-based carbon content: 49%, MFR (190℃, load 2.16kg): 5g / 10min, Mw: 170,000)

[0142] Aliphatic polyester 2 Polylactic acid (PLA): NatureWorks "Ingeo 4032D" (Bio-based carbon content: 99%, MFR (210℃, load 2.16kg): 7g / 10min, Mw: 180,000)

[0143] Inorganic fillers Talc: "Microace K-1" manufactured by Nippon Talc Co., Ltd. (This talc does not contain carbon atoms, so it does not affect the evaluation of the bio-based carbon content of the resin composition.)

[0144] Lubricants Erucamide: Mitsubishi Chemical Corporation's "Diamid L-200" (bio-based carbon content: 0%)

[0145] <Production of Aliphatic-Aromatic Polyester 1> [Production Example 1] In a reaction vessel equipped with a stirrer, a nitrogen inlet, a heater, a thermometer, and a pressure reducing port, 110 parts by mass of succinic acid (derived from biomass), 127 parts by mass of terephthalic acid (derived from petroleum), 168 parts by mass of 1,4-butanediol (derived from petroleum), and 0.46 parts by mass of trimethylolpropane were charged as raw materials, 4 parts by weight of a 1,4-butanediol solution in which 5% by weight of tetra-n-butyl titanate had been dissolved in advance, and 6.6 parts by weight of a 1,4-butanediol solution in which 2% by weight of magnesium acetate tetrahydrate had been dissolved in advance. The molar ratio of succinic acid to terephthalic acid was 55:45, the molar ratio of 1,4-butanediol to the total molar amount of succinic acid and terephthalic acid was 1.1, and trimethylolpropane was 0.10 molar relative to the total structural units of the polymer to be produced. The percentage was set at 100%. Nitrogen gas was introduced into the vessel while stirring the contents of the vessel, and the system was conditioned under a nitrogen atmosphere by vacuum replacement. Next, the temperature was raised to 185°C while stirring the system, and the reaction was carried out at this temperature for 45 minutes to 1 hour. Next, the temperature was raised to 220°C over 1 hour and 30 minutes. Thereafter, the temperature was raised to 230°C over 1 hour, and at the same time, the pressure was reduced to 0.07 kPa or less over 1 hour and 30 minutes, and polymerization was continued while maintaining the heated and reduced pressure state, and polymerization was terminated when a predetermined viscosity was reached, and an aliphatic-aromatic polyester 1 was obtained.

[0146] <Film manufacturing> The raw materials were mixed in the ratio shown in Table 1, melt-kneaded in a twin-screw extruder with a screw diameter of 30 mm at a set temperature of 150° C., and pelletized to obtain a resin composition. This resin composition was fed to a single-screw extruder with a screw diameter of 40 mm, and extruded upward in a bubble form from an annular die with a diameter of 60 mm and a die lip gap d shown in Table 1 so as to obtain a blow ratio B shown in Table 1. The extrusion was air-cooled with a cooling ring, and the extrusion was taken up at 10 m / min while being folded by nip rolls above the die, and a film was wound up. D / (B 2 A film with a thickness of t = 0.03 mm was obtained so that the relational expression (t x t) was the value shown in Table 1. The set temperatures of the screw and die were appropriately adjusted between 160 and 180°C so as not to cause excessive load on the screw.

[0147] [Table 1]

[0148] From Table 1, AP max / AP оrg Films with a tear strength of 1.25 or more have a large difference between the tear strength in a specific direction and the tear strength in the perpendicular direction, and this indicates that the films are excellent in terms of ease of linear tearing in one direction.

Claims

1. A film made of a resin composition containing an aliphatic-aromatic polyester, Contains 20% by mass or more of an aliphatic-aromatic polyester, the aliphatic-aromatic polyester comprises constitutional units derived from terephthalic acid, Among the anisotropy parameters AP obtained by measuring the polarized Raman spectrum of the film surface, AP measured by the following evaluation method max and AP оrg The ratio AP max / AP оrg is 1.25 or greater. (Evaluation Method) In a laser micro-Raman spectrometer, linearly polarized laser light having a wavelength of 633 nm and a polarization direction (electric field vibration direction) set at an arbitrary angle by inserting a ½ λ plate into the laser light is made to enter the film surface perpendicularly, and the spectrum of the generated Raman scattered light is measured. -1 The area of ​​the Raman band having a peak near I 1612 and 2850 cm corresponding to the stretching vibration of the methylene group in the polymer chain. -1 The area of ​​the Raman band having a peak near I 2850 In this case, among the directions of the arbitrary angle, I 1612 / I 2850 The anisotropy parameter measured in the direction where the ratio expressed by is maximum is AP max and the anisotropy parameter measured in a direction perpendicular to the direction is AP оrg Let us assume that.

2. The AP measured according to ISO 6383-2 max The tear strength in the direction in which the tear strength was measured divided by the thickness of the film (TR 1 ) is 70 N / mm or more, оrg The tear strength in the direction in which the tear strength was measured divided by the thickness of the film (TR 2 ) is TR 1 2. The film of claim 1, wherein the thickness of the film is 1 / 10 or less.

3. The film of claim 1 , wherein the resin composition further comprises an aliphatic polyester.

4. The film according to claim 3 , wherein the aliphatic polyester is a polyester containing an aliphatic diol unit and an aliphatic dicarboxylic acid unit as main constituent units.

5. The film according to claim 4 , wherein the aliphatic polyester contains, as a constituent unit, one or more aliphatic dicarboxylic acid units selected from the group consisting of succinic acid units, adipic acid units, and sebacic acid units.

6. 2. The film of claim 1, wherein the aliphatic-aromatic polyester comprises constitutional units derived from 1,4-butanediol and constitutional units derived from succinic acid.

7. 2. The film of claim 1, wherein the resin composition has a bio-based carbon content of 20% or greater as measured in accordance with ISO 16620-2.

8. An easily openable packaging material comprising the film according to any one of claims 1 to 7.

9. A method for producing the film according to any one of claims 1 to 7, comprising the steps of: The method includes a molding step of extruding the resin composition containing the aliphatic-aromatic polyester through a die lip and performing inflation molding to obtain a film, In the molding step, the gap d (mm) of the die lip, the blow ratio B, and the thickness t (mm) of the molded film satisfy the following relationship represented by formula (1): A method for manufacturing a film. d / (B 2 ×t)≧3 (1)

Citation Information

Patent Citations

  • Biodegradable maturing film and method for producing the same

    JP2007002011A